Metal toxicity and recovery response of riverine periphytic algae - Pandey L.K.; Bergey E.A. (My University, 2025)
In the present study, in situ assessment of metal (Cu and Zn) toxicity followed by their recovery response was examined in periphyton dominated by diatoms. For doing so, metal diffusing substrates (MDS) were constructed and deployed in the river water for 6 weeks (3 weeks stress and 3 weeks recovery after replacing metal solution from the MDS). The use of MDS ensured that colonised periphyton on metal diffusing and control substrates were exposed to similar environmental conditions. The metal toxicity and recovery response of the community was examined in terms of traditional algal community parameters (biovolume, species richness, Shannon index, relative abundance) as well as with the newer non-taxonomical parameters (deformities and lipid bodies in diatoms). Both traditional and non-taxonomical parameters indicated complete recovery (from metal toxicity) of periphytic communities after 3 weeks following the withdrawal of Cu and Zn solution from the diffusing substrates. Newer non-taxonomical parameters, such as, deformities and lipid bodies, provide a new insight to understand metal toxicity and recovery response of diatom assemblages (the dominant autotrophs in the periphyton community) because these features are directly visible in live frustules, need no expertise in identification of diatoms and can be globally assessed with simple protocol. The experimental loss of metal pollutants and the constant immigration of algae (not previously exposed to high levels of metals) in fluvial systems aided periphyton recovery. Lastly, it is found that periphytic biofilms (dominated by diatoms) proved to be good bioindicators of metal toxicity and recovery in fluvial ecosystem. © 2018 Elsevier B.V.